PENDAMPINGAN KUALITAS KEPEMIMPINAN BISNIS PADA USAHA PANDAI BESI DESA KEDATON - Azhari; Retno Muslinawati; Tengku Muda Agam Sakti; Wizka Rif'atul Izah (Jurnal Abdi Masyarakat, 2025)
Leadership quality mentoring in blacksmith businesses in Kedaton Village aims to improve the leadership and managerial capacity of business actors to be more professional and competitive. This mentoring is carried out using a Need-Based Approach, which focuses on improving understanding of the vision, mission, and managerial strategy. The evaluation results show that business actors have improved in formulating clearer business directions, optimizing resource management, and increasing production and marketing efficiency. In addition, there have been positive changes in strategic decision-making, communication with workers, and the ability to adapt to market dynamics. Despite challenges such as limited access to capital and technology, this mentoring has helped business actors build a more structured business system. The implications of this mentoring are increased business competitiveness, higher productivity, and strengthening the local business ecosystem